(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The article articulates the laboratory in movement on dream enunciations with Solomonova and Wei’s (2016) neurophenomenological theory, María Zambrano’s reflections on the oneiric dimension of reason, and PPGAC/UDESC’s research "Bodying the Oneiric" on performative methodologies for dreaming bodies. This transdisciplinary intersection investigates dream depth as protagonist through embodied affect, proposing approaches that integrate neuroscience, philosophy and performative arts in understanding oneiric experience as a simultaneously mental, somatic and creative phenomenon.